Response surface optimization of UV/H2O2-based photo-oxidative degradation of amoxicillin - Wahyu Zuli Pratiwi; H. Hadiyanto; W. Widayat (Results in Engineering, 2024)
The use of antibiotics has increased in the last five years due to the COVID-19 pandemic, which has led to an increase in antibiotic concentrations in wastewater. Therefore, there is a need for the implementation of technology for antibiotic degradation. This research aimed to determine the efficiency of the advanced oxidation process (AOP) using a combination of UV/H2O2 for antibiotic degradation. The degradation was conducted using the antibiotic amoxicillin in a batch-wise experiment. Response Surface Methodology with Central Composite Design (RSM-CCD) was employed to optimize the efficiency of the degradation process. The result revealed that the degradation rate constants and efficiency using UV/H2O2 were 0.0127/min and 62.43 %, respectively, which was higher than that of UV (0.0043/min and 30.524 %) or H2O2 (0.0033/min and 20.365 %) after 90 min of treatment. The optimum solution was achieved at an initial pH of 4.2, an amoxicillin concentration of 45.85 mg/L, and an H2O2 concentration of 10.093 mM. Under these optimal conditions, the degradation efficiency of amoxicillin could reach 99.98 %. In addition, the results of the study demonstrate the inhibitory effect of the degraded amoxicillin on pathogenic bacteria, thus indicating that the photochemical oxidation process can effectively degrade amoxicillin residues in wastewater. This study showed that photochemical oxidation has the potential to be an effective approach for antibiotic degradation.